Reflexiones sobre la contribución de la tutoría al futuro del aprendizaje - Elmore, Richard (2016)
In late October and early November I helped organize a workshop for tutoring promoters in the state of Guanajuato, Mexico. The purpose of the workshop was to involve adult mentoring promoters in the first efforts to more explicitly generate rules and practices on the role of both adults and young people in mentoring work. So far, tutoring has spread widely, in individual demonstrations, face-to-face and in possible professional development sessions, but without the explicit intention of codifying the practice. The Guanajuato workshop was expressly conceived to see if a more explicit formulation of the tutoring practice would help to develop the new way of teaching and learning as well as accelerating its dissemination.